The role of femtolaser in cataract surgery - Nagy, Zoltán; Szaflik, Jacek P. (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
Having been very successful in corneal surgery, femtolasers were recently introduced into the surgery of crystalline lens. The most important indications and advantages include: perfectly centered and sized capsulotomy, liquefaction of softer lenses and fragmentation of harder lenses which allows for chopping the nucleus without the use of phaco energy. Femtolaser can also be used for creating corneal wounds (tunnels) of any size at any location, and in order to manage the preoperative astigmatism using arcuate incisions at the desired depth within the cornea. Because of controlled steps in cataract surgery, wide acceptance and spread is to be expected.